Genital anatomy and copulatory interactions in the broad snouted Caiman (Caiman latirostris). Issue 10 (8th July 2021) - Moore, Brandon C.; Kelly, Diane A.; Piva, Milan; Does, Mark; Kim, Dong Kyu; Simoncini, Melina; Leiva, Pamela M.L.; Pina, Carlos I.
Abstract: The broad snouted caiman is a crocodylian native to South America that is subject to extensive conservation management in both wild and farming environments. Although reproductive behaviors like egg laying and clutch care have been examined in this species, little else is known about their copulatory system. We examined the anatomy of male and female cloacal and genital tissues ex vivo to build hypotheses of their interactions during copulation and the effects of that interaction on insemination. Male phallic glans tissues were artificially inflated to expand into their copulatory state, allowing the examination and quantification of structural changes at the gross and tissue levels. Digital reconstruction of MRI stacks yielded three‐dimensional tissue compartment specific glans models of the inflated state. Silicone molds of female cloacae and oviducts in conjunction with dissection and diceCT analysis allowed us to assess internal geometry and infer how male and female features interact in copulo . We observed glans expansion within the female proctodeum would result in a copulatory lock limiting deeper intromission or retraction. Intromission and subsequent creation of the copulatory lock produces extensive clitoral compression, providing a possible mechanism for female assessment of male copulatory performance. Further, glans expansion forms a distal lumen that positions the glans tip in or near the vaginal openings. A coiled, muscular vagina provides a possible mechanism for postcopulatory sexual selection by excluding semen. Together, the complex male–female interaction supports evidence for cryptic selection by female choice, which can act as a driver of genital coevolution.